A REFINED SOLUTION TO THE FIRST TERRESTRIAL PB-ISOTOPE PARADOX - Murphy D.T.; Kamber B.S.; Collerson K.D. (My University, 2003)
The first terrestrial Pb-isotope paradox refers to the fact that on average, rocks from the Earth's surface (i.e. the accessible Earth) plot significantly to the right of the meteorite isochron in a common Pb-isotope diagram. The Earth as a whole, however, should plot close to the meteorite isochron, implying the existence of at least one terrestrial reservoir that plots to the left of the meteorite isochron. The core and the lower continental crust are the two candidates that have been widely discussed in the past. Here we propose that subducted oceanic crust and associated continental sediment stored as garnetite slabs in the mantle Transition Zone or mid-lower mantle are an additional potential reservoir that requires consideration. We present evidence from the literature that indicates that neither the core nor the lower crust contains sufficient unradiogenic Pb to balance the accessible Earth. Of all mantle magmas, only rare alkaline melts plot significantly to the left of the meteorite isochron. We interpret these melts to be derived from the missing mantle reservoir that plots to the left of the meteorite isochron but, significantly, above the mid-ocean ridge basalt (MORB)-source mantle evolution line. Our solution to the paradox predicts the bulk silicate Earth to be more radiogenic in Pb-207/Pb-204 than present-day MORB-source mantle, which opens the possibility that undegassed primitive mantle might be the source of certain ocean island basalts (OIB). Further implications for mantle dynamics and oceanic magmatism are discussed based on a previously justified proposal that lamproites and associated rocks could derive from the Transition Zone.
Keywords: Pb isotopes; paradox; mantle Transition Zone; undegassed mantle; core formation